The Effect of Workload on Turnover Intention Level of Employees at The Westin Resort Nusa Dua Bali - Putu Lisa Mahrtini; Wirata, I Nengah; Paramita, Ratri (PT FORMOSA CENDEKIA GLOBAL, 2024)
An important factor in determining whether a business can successfully achieve its goals is its human resource management. Companies must pay attention to their employees to prevent them from wanting to leave due to perceived excessive workloads. This study was conducted at The Westin Resort Nusa Dua Bali with the aim of understanding the impact of workload on employee turnover rates. The sample population in this study consisted of all 471 employees, and using the Slovin formula, a sample of 82 respondents was obtained. The sampling technique used was purposive sampling. Data collection was carried out by distributing questionnaires with a 5-point Likert scale. The data analysis techniques used included validity and normality tests, classical assumption tests, simple linear regression analysis, t-test, multiple linear regression analysis, F-test, and the determination coefficient test, all processed using SPSS version 26 for Windows.The results of the study showed that tcalculated>ttablet_calculated > t_tabletcalculated>ttable (35.652 > 1.664) and the significance value <α< α< 0.05), thus Ho is rejected and H1 is accepted. This indicates a significant impact of workload on employee turnover at The Westin Resort Nusa Dua Bali. It can be concluded that workload (X) has a positive and significant effect on turnover at The Westin Resort Nusa Dua Bali. The determination coefficient test results state that the workload contributes 94.5%, while the remaining 5.5% is explained by other variables not included in this study.